(3GdeGdjI GdYGeI (B: s (3eWHhYI ehLgI dWdHI GdSfI GdKGfjI Ydhe GbJUGOjI (B/ s - (3GdLhRj, ZfjIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3GdJWhQ GdJGQjNj ddeGdjI GdYGeI h YdGbJgG HGdYdhe GdCNQi , GdfabGJ GdYGeI , XGgQI JRGjO GdfabGJ GdYGeI , GdGjQGOGJ GdYGeI ,GdVQGFH ,GdbQV GdYGe h GdejRGfjI GdYGeI (B.s
(3eQGLY U(B.116s
Keywords: (3GdeGdjI GdYGeIs; (3GdejRGfjIs; (3GdfabGJ GdYGeIs